The Influence of Compensation and Work Motivation on Employee Job Satisfaction at Montigo Resorts Nongsa Batam - Rezka Makhfirah; Khairani Saladin (Journal of Multidimensional Management, 2025)
This study aims to analyze the effect of compensation and work motivation on employee job satisfaction at Montigo Resorts Nongsa Batam. A quantitative research method with a causal associative approach was employed, involving 130 permanent employees as respondents selected through a survey. Data were collected using an online questionnaire and analyzed using multiple linear regression with the assistance of SPSS version 25. The findings reveal that job satisfaction was categorized as very good (mean score = 4.21), compensation was also in the very good category (4.25), and work motivation was in the very good category as well (4.28). Partial tests indicate that compensation has a significant effect on job satisfaction, and work motivation also has a significant effect. Simultaneous testing demonstrates that compensation and work motivation jointly exert a significant effect on job satisfaction, with an F- value of 12.710 exceeding the critical value of 3.07 and a significance level of 0.000 (<0.05). The Adjusted R² value of 0.154 indicates that 15,4% of the variance in job satisfaction is explained by compensation and work motivation, while the remaining 84,6% is influenced by other factors beyond the scope of this study.